Rationale, Methods, Feasibility, and Preliminary Outcomes of a Transdiagnostic Prevention Program for At-Risk College Students - Burke, Anne S.; Shapero, Benjamin G.; Pelletier-Baldelli, Andrea; Deng, Wisteria Y.; Nyer, Maren B.; Leathem, Logan; Namey, Leah; Landa, Carrie; Cather, Corinne; Holt, Daphne J. (Frontiers in Psychiatry, 2020)
Purpose: Early adulthood represents one period of peak risk for the onset of serious mental illnesses. The college campus provides a unique opportunity to assess and monitor individuals in this at-risk age group; however there are no validated early detection programs that are widely implemented on college campuses. To address this gap, we designed and tested an early detection and prevention program tailored to the needs of college students. A transdiagnostic approach was employed given recent evidence for shared risk factors across major mental illnesses. Design: Single arm, prospective study evaluating outcomes pre- and post- a 4-week intervention. Method: Three in-person mental health screenings were conducted on the campus of an urban university. Undergraduate students with at least mildly elevated scores on a self-report measure of depression and/or subclinical psychotic symptoms, who were not receiving treatment for these symptoms, were invited to participate in a 4-session workshop focused on increasing self- and other- awareness using established mindfulness, self-compassion, and mentalization principles and experiential exercises. Symptoms, resilience-promoting factors, and aspects of social functioning were assessed pre- and post- intervention. Results: Of the 416 students screened, 146 (35%) were eligible for the workshop. A total of 63 students participated in the workshop and 91% attended at least 3 of the 4 sessions. Significant pre-to-post reductions in symptoms (depression, anxiety and subclinical psychotic symptoms, ps < 0.004) and improvements in resilience-related factors (self-compassion and self-efficacy, ps < 0.006) and indices of social functioning (social motivation, activity, and a measure of comfort with the physical presence of others, ps < 0.04) were observed. Moreover, the significant increases in resilience-related factors correlated with the reductions in affective symptoms (ps < 0.03). Also, the majority of participants found the workshop interesting, useful and would recommend it to a friend. Conclusions: These findings suggest that a brief on-campus mental health screening and early intervention program is feasible, acceptable, and may produce immediate increases in resilience-related skills and related symptom reductions. Follow-up work will determine whether this program can improve longer-term outcomes, such as school retention, academic performance and need for psychiatric care, in this at-risk population.